2017
DOI: 10.1002/ece3.3579
|View full text |Cite
|
Sign up to set email alerts
|

An integrative mating system assessment of a nonmodel, economically important Pacific rockfish (Sebastes melanops) reveals nonterritorial polygamy and conservation implications for a large species flock

Abstract: Characterizing the mating systems of long‐lived, economically important Pacific rockfishes comprising the viviparous Sebastes species flock is crucial for their conservation. However, direct assignment of mating success to sires is precluded by open, offshore populations and high female fecundity. We addressed this challenge by integrating paternity‐assigned mating success of females with the adult sex ratio (ASR) of the population, male evolutionary responses to receptive females, and reproductive life histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 104 publications
(151 reference statements)
0
2
0
Order By: Relevance
“…Different mating systems vary in their sexual selection mechanisms (i.e., competition for mating through same‐sex combat and opposite‐sex mate choice), resulting in differences in the intensity and direction of sexual selection (i.e., greater on males or females) which affects the mating and reproductive success of a population (Arnold & Wade, 1984; Jones, 2009). Consequently, mating systems can drive morphological, behavioral, and physiological evolution, and create sexual conflict (Warner et al 1995; reviewed in Auld, 2018; Karageorge & Wilson, 2017). Many previous studies of mating systems have been based on observations of social behaviors, which can only explain the social mating system and not the genetic mating system, which specifies biological parentage of offspring (Jones & Ardren, 2003; Jones & Avise, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Different mating systems vary in their sexual selection mechanisms (i.e., competition for mating through same‐sex combat and opposite‐sex mate choice), resulting in differences in the intensity and direction of sexual selection (i.e., greater on males or females) which affects the mating and reproductive success of a population (Arnold & Wade, 1984; Jones, 2009). Consequently, mating systems can drive morphological, behavioral, and physiological evolution, and create sexual conflict (Warner et al 1995; reviewed in Auld, 2018; Karageorge & Wilson, 2017). Many previous studies of mating systems have been based on observations of social behaviors, which can only explain the social mating system and not the genetic mating system, which specifies biological parentage of offspring (Jones & Ardren, 2003; Jones & Avise, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies employing genetic paternity analysis have demonstrated that rockfishes can be polyandrous (documented in at least 15 species to date), with as many as four sires per brood observed in studies of wild fishes and as many as six sires per brood observed in studies of captive fishes (Gao et al ., 2017; Gray et al ., 2015; Hyde et al ., 2008; Johansson et al ., 2012; Karageorge & Wilson Jr., 2017; Sogard, Gilbert‐Horvath, et al ., 2008; Van Doornik et al ., 2008). This may be a diversified bet‐hedging strategy when mate selection criteria are uncertain (Yasui, 1998, Hyde et al ., 2008, Sogard, Gilbert‐Horvath, et al ., 2008, Johansson et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%